2015
DOI: 10.1111/sms.12536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training with moderate vs heavy loads on muscle mass and strength in the elderly: A meta‐analysis

Abstract: The purpose of the present study was to perform a meta-analysis to compare the efficacy of heavy (∼80% of one repetition maximum, 1RM) vs light-moderate load (∼45% 1RM) resistance training (RT) programs in inducing strength gains and skeletal muscle hypertrophy in elderly people. To assess the role of training volumes, studies in which training protocols were matched for mechanical work were independently analyzed. In all 15 studies included (448 subjects, age 67.8 years), when comparing heavy with light-moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 77 publications
(147 reference statements)
7
142
3
10
Order By: Relevance
“…Thus, when approximately 20 exercise repetitions are performed, which is common in clinical practice, ultra-short-term HRV analysis appears feasible (14). Because resistance exercises for the elderly promote the gain of bone and muscle mass and the improvement of cardiovascular behavior, physical capacity, and quality of life, studies that assess HRV during experimental exercise programs appropriate for the training of this population are of great importance (34). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, when approximately 20 exercise repetitions are performed, which is common in clinical practice, ultra-short-term HRV analysis appears feasible (14). Because resistance exercises for the elderly promote the gain of bone and muscle mass and the improvement of cardiovascular behavior, physical capacity, and quality of life, studies that assess HRV during experimental exercise programs appropriate for the training of this population are of great importance (34). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, it promotes muscle function, which is helpful to prevent declines in the ability to complete activities of daily living [10]. A recent meta-analysis has shown that a sufficient amount of resistance training, even light load intensity training, leads to improvements in muscle function in older adults [11]. In addition, to maintain or improve muscle function, older adults must continue their physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…For the management of sarcopenia, there is a strong recommendation that individuals with sarcopenia should be enrolled in a resistance exercise programme. There is a reasonable amount of evidence that resistance exercise will increase both muscle mass and strength . The use of a protein rich diet (1 to 1.5 g/day) or protein supplementation received a conditional recommendation based on a small amount of evidence and a previous consensus conference .…”
Section: Management Of Sarcopeniamentioning
confidence: 99%